Upaya Meningkatkan Kepuasan Karyawan Berdasarkan Matriks Cartesius di Provinsi Jawa Timur - Mumun Zurida Emilia; Djazuli Chalidyanto; Ika Dhonarista (Media Gizi Kesmas, 2023)
Background: It is known that there was a decrease in the percentage of employee satisfaction in 2013-2014 which refers to cultural aspects such as career opportunities, promotion opportunities, communication, leadership, work activities, work environment, and compensation or awards by 2.36%. This also applies to the increase in job satisfaction in East Java Province, where there are many employees or workers in the area. Objectives; This study was structured with the aim of building an effort to increase employee job satisfaction based on the Cartesian matrix at one of the hospitals in East Java, namely Menur Mental Hospital in Surabaya, East Java. Methods: The method used in this research is descriptive observational with a cross-sectional study design. Results: The results showed that there was a gap between expectations and perceptions of the attributes and sub-attributes of job satisfaction. On the other hand, the results showed that most mental hospital employees were dissatisfied with job satisfaction attributes, especially for the 26-35 years age group, female, D3 education, working period of more than 7 years, civil servant, and status. Conclusions: The analysis of n on the Cartesian matrix through the communication attributes of job satisfaction with sub-attributes refers to improvement priority efforts.